Recommended Diet for Diabetics Hydrocarbons, Glycemic Impact, Glycemic Load, Glycemic Index, and Mediterranean Diet - Rehan Haider; Asghar Mehdi; Geetha Kumari; Zameer Ahmed; Sambreen Zameer (Contemporary Journal of Applied Sciences, 2024)
The growing prevalence of diabetes has necessitated the development of effective digestive blueprints to increase blood glucose levels and improve overall well-being. This study aimed to determine the impact of various dietary elements and abstinence from food patterns on glycemic control in diabetic inmates. Specifically, it tests the parts of hydrocarbons, glycemic impact, glycemic load, glycemic index, and the ability of the Mediterranean diet to consume diabetes. The research methodology involved an inclusive composition review and meta-reasoning of the existing studies that concentrated on these factors. Data were obtained from dispassionate tests, practical studies, and digestive directions written in peer-reviewed journals. The verdicts indicate that diets high in complex carbohydrates and texture, accompanied by a reduced glycemic index and glycemic load, are advantageous in controlling blood glucose levels. The Mediterranean diet, resulting from the extreme use of products that produce whole grains and healthy fats, is specifically productive for reconstructing glycemic control and lowering cardiovascular risk determinants. Furthermore, the study highlights the significance of the individualized ability to consume pieces of advice to establish the glycemic reaction of various cookings, seeing the variability in individual metabolic reactions. The results imply that merging these digestive elements into regular food planning can considerably improve diabetes administration and overall well-being